Uji Pupuk Organik untuk Pertumbuhan Cabai Keriting pada Tanah Miskin Hara - Risal, Darmawan (Jurnal Ecosolum, 2020)
This study aims to test solid organic fertilizer on the growth of curly red chili. The method used is a Randomized Block Design with planting on dry land by making beds measuring 1 m x 7 m and spacing of 60 cm x 50 cm. The treatments are P1 (Giving organic fertilizer of horse manure resulting from burning), P2 (Giving organic fertilizer of cow manure), P3 (Giving organic fertilizer of chicken manure) and P4 (Giving of organic compost artificial fertilizer) repeated 3 times by giving the same fertilizer dose (18, 93 ton ha-1). Data analysis used analysis of variance (Duncan α 0.05 test). The highest crop research results were P4 and the lowest was P2. The results of the study of the growth of the number of leaves there are significant differences in the treatment of P1 to treatment P2 and P4 but do not have a significant effect on the treatment of P3. The highest average yield of chili is in P4 and the lowest is in P2. On fruit length growth shows a real influence, where P4 has the highest and lowest yield is P2. Similarly, in the growth of the number of fruits where P4 has the highest and lowest treatment P2. These results indicate a  real effect on each treatment. Based on the results of the study it can be concluded that the  combustion  of horse manure organic fertilizer has the same real effect as organic manure of  chicken  manure and artificial compost on the growth of chilli plant height and has the same  effect    as organic fertilizer of chicken manure on the growth of the number of leaves. As for fruit  production, organic fertilizer horse manure has a real effect with all treatments.